Effects of the COVID-19 pandemic on noise pollution in three protected areas in metropolitan Boston (USA). (April 2021) - Terry, Carina; Rothendler, Matthew; Zipf, Lucy; Dietze, Michael C.; Primack, Richard B.
Abstract: Noise pollution can reduce the ability of urban protected areas to provide a refuge for people and habitat for wildlife. Amidst an unprecedented global pandemic, it is unknown if the changes in human activity have significantly impacted noise pollution in metropolitan parks. We tested the hypothesis that reduced human activity associated with the COVID-19 pandemic lockdowns would lead to reduced sound levels in protected areas compared with non-pandemic times. We measured sound levels in three urban protected areas in metropolitan Boston, MA (USA) at three time periods: in the fall and summer before the pandemic, immediately after the government-imposed lockdown in March 2020 when the trees were leafless, and during the beginning of reopening in early June 2020 when the trees had leaves. At all time periods, sound levels were highest near major roads and demonstrated a logarithmic decrease further from roads. At the two protected areas closest to the city center, sound levels averaged 1–3 dB lower during the time of the pandemic lockdown. In contrast, at the third protected area, which is transected by a major highway, sound levels were 4–6 dB higher during the time of the pandemic, likely because reduced traffic allowed vehicles to travel faster and create more noise. This study demonstrates that altered human levels of activity, in this case associated with the COVID-19 pandemic, can have major, and in some cases unexpected, effects on the levels of noise pollution in protected areas. Highlights: Sound in urban protected areas was monitored before and during COVID-19 lockdown. Park soundscapes were modeled based on lockdown stage and distance from roads. Sound levels decreased in two parks and increased in one park during lockdown. Sound levels were highest near roads and decreased with distance from roads. COVID-19 noise pollution is affected by traffic speeds and timing of tree leaf out.